122k views
17 votes
Help help me help help please help help me help help please help help

Help help me help help please help help me help help please help help-example-1
User Ben Allred
by
5.6k points

1 Answer

4 votes

Explanation:


\large{ \star \fcolorbox{magenta}{purple}{ \fcolorbox{magenta}{blue}{ \fcolorbox{magenta}{pink}{ \fcolorbox{magenta}{red}{ \sf{ 13}}}}}} \star


{x}^(2) - 26x + 169 = 0 \\ {x}^(2) - 13x -8 13x + 169 = 0 \\ ( {x}^(2) { - 13}^(2) ) = 0 \\ {x}^(2) = 0 + {13}^(2) \\ {x}^(2) = {13 }^(2) \\ x = \sqrt{ {13}^(2) } \\ x = 13

User Yeqing Zhang
by
6.2k points